Pregnancy outcomes of women whom spouse fathered children after tyrosine kinase inhibitor therapy for chronic myeloid leukemia A systematic review - Szakács Zsolt (PLOS ONE, 2020)
The introduction of tyrosine kinase inhibitors (TKIs) has revolutionized the therapy of chronic myeloid leukemia (CML). Although the efficacy of TKIs is beyond dispute, conception-related safety issues are still waiting to be explored, particularly in males. This systematic review aimed to summarize all available evidence on pregnancy outcomes of female spouses of male CML patients who fathered children after TKI treatment for CML.We performed a systematic search in seven electronic databases for studies that reported on male CML patients who did or did not discontinue TKI treatment before conceiving, and the pregnancy outcomes of their female spouse are available. The search centered on the TKI era (from 2001 onward) without any other language or study design restrictions.Out of a total of 38 potentially eligible papers, 27 non-overlapping study cohorts were analyzed. All were descriptive studies (case or case series studies). Altogether, 428 pregnancies from 374 fathers conceived without treatment discontinuation, 400 of which (93.5%) ended up in a live birth. A total of ten offspring with a malformation (2.5%) were reported: six with imatinib (of 313 live births, 1.9%), two with nilotinib (of 26 live births, 7.7%), one with dasatinib (of 43 live births, 2.3%), and none with bosutinib (of 12 live births). Data on CML status were scarcely reported. Only nine pregnancies (from nine males) and no malformation were reported in males who discontinued TKI treatment before conception.Malformations affected, on average 2.5% of live births from fathers who did not discontinue TKI treatment before conception, which is comparable with the rate of malformations in the general population. Large-scale studies with representative samples are awaited to confirm our results.